Analysis of induced abortion-related complications in women admitted to the Kinshasa reference general hospital: a tertiary health facility, Democratic Republic of the Congo - Daniel Ishoso Katuashi; Antoinette Kitoto Tshefu; Yves Coppieters (BMC, 2018)
Abstract Background Due to a lack of relevant data on induced abortions in the Democratic Republic of the Congo (DRC) as well as the persistence of maternal deaths in the country, this study aims to analyse the induced abortion-related complications in women who were admitted to the Kinshasa Reference General Hospital (KRGH). Methods This is a cross-sectional study on 368 obstetric and gynecological patients who were admitted, as emergency cases, to the KRGH during 2014. This health facility was selected because it is a tertiary health facility with an obstetric and gynecological emergency unit most used in the city of Kinshasa. Patient data were collected from patient records and analyzed. Results From the 368 patients admitted to receive obstetric and gynecological emergency care services in 2014 at the KRGH, 12.2% (95% CI: 9.1-16.1%) had complications due to induced abortion that was significantly diagnosed to adolescents (p <  0.001), single or separated or divorced women or widow(p <  0.001), and to patients with history of one or several induced abortions(p <  0.001). The median duration of hospitalization was ten days and this period of time was significantly longer for the patients who underwent surgery for pelvic peritonitis due to uterine perforation(p <  0.001) compared with the group of patients who underwent Caesarean section/hysterectomy. The mortality rate related to them is 37.8% (95% CI: 23.8-53.5%) with an increase of risk of death in the presence of a post-abortive pelvic peritonitis-type complication, 56.3% of deaths occurred after two days of hospitalization. Conclusion The complications of induced abortions are a major public health problem due to its frequency among patients admitted to the KRGH, as well as the poor medical management, and mortality percentage related to them. Therefore, there is a need to understand the reason for the poor medical management to fill in and provide an adequate intervention package.